Issues Of Sustainable Development Of Small Business And Entrepreneurship In The Digital Economy - Toxirjonov, Doniyor (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This thesis analyzes the issues of sustainable development of small business and entrepreneurship in the digital economy. The work studies the impact of digital technologies on small business, the possibilities of creating new business models, and ways to increase the efficiency of production and services. The thesis also highlights the importance of technological preparation, training of qualified personnel, and financial and legal support in the sustainable development of small business. The research results show that the sustainable development of small business in the digital economy is an important factor for the country's economic growth, and practical recommendations are given for the development of this sector.